2020
DOI: 10.1159/000509197
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endoscopic Ultrasound in Pancreatic Cancer Staging in the Era of Neoadjuvant Therapy and Personalised Medicine

Abstract: Precise staging of pancreatic cancer is crucial for treatment choice. In clinical practice, this includes the TNM staging and determination of tumour resectability, based on a multimodality imaging workup. International guidelines recommend multi-detector computed tomography (CT), with a dedicated pancreatic protocol, as the first-line tool for TNM staging and evaluation of tumour-vessel relationships. In non-metastatic disease upon initial CT assessment, both magnetic resonance imaging and endoscopic ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This approach has surpassed percutaneous sampling techniques, as it provides tissue core biopsies, allowing histological assessment. New generation FNB needles demonstrated a diagnostic accuracy of over 95% for solid pancreatic lesions and provide samples appropriate for ancillary testing, such as immunohistochemistry and tumor molecular profiling [25,31].…”
Section: Discussionmentioning
confidence: 99%
“…This approach has surpassed percutaneous sampling techniques, as it provides tissue core biopsies, allowing histological assessment. New generation FNB needles demonstrated a diagnostic accuracy of over 95% for solid pancreatic lesions and provide samples appropriate for ancillary testing, such as immunohistochemistry and tumor molecular profiling [25,31].…”
Section: Discussionmentioning
confidence: 99%
“…The authors believe that EUS should be integrated, using an evidence-based approach, into the diagnostic and therapeutic spectrum of multidisciplinary pancreas centers as soon as possible. The literature has provided convincing evidence of its usefulness in diagnostics and as a valuable addition to the therapeutic armamentarium [ 6 , 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are four types of vascular involvement in pancreatic cancer: type 1, clear invasion with the encasement of a vessel by a tumor; type 2, a tumor that is in contact with a vessel with the loss of the hyperechoic vessel layer with or without vessel irregularity or luminal narrowing; type 3, a tumor that contacts a vessel without the loss of the hyperechoic vessel layer; and type 4, clear non-invasion with distance between the tumor and vessel [21]. Apart from that, tumor thrombus within the vessel or the presence of collaterals surrounding the tumor can also be found [22] (Figure 1). For N staging, a meta-analysis has also shown that EUS has a better sensitivity (58% vs. 24%) and a similar specificity (85% vs. 88%) to those of CT in detecting lymph node involvement [23,24].…”
Section: Role Of Eus In the Staging Of Tumorsmentioning
confidence: 99%